The association between caffeine and alcohol consumption and IVF/ICSI outcomes: A systematic review and dose–response meta‐analysis - Wentao Rao; Yuying Li; Nijie Li; Qingyun Yao; Yufeng Li (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The objective of this study was to evaluate the association between caffeine and alcohol consumption and in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) outcomes. Material and methods The protocol was registered in the PROSPERO database on May 23, 2021 (registration number: CRD42021256649), and updated on August 4, 2022. Two researchers performed a literature search in the PubMed, Embase, and MEDLINE databases for articles published before July 15, 2022 independently. Studies investigating the association between caffeine and alcohol consumption and IVF/ICSI outcomes were included, and studies reporting the consumption amount were analyzed using a one‐stage robust error meta‐regression‐based method to explore potential dose–response relation. Funnel plot was used to assess publication bias if more than 10 studies were included. Results Twelve studies on caffeine consumption and 14 studies on alcohol consumption were included in the systematic review, of which seven and nine were eligible for the meta‐analysis. These studies included 26 922 women and/or their spouses who underwent IVF/ICSI treatment. Women's and men's caffeine consumption was not significantly associated with the pregnancy rate (odds ratio [OR] 0.97, 95% confidence interval [CI] 0.85–1.12; OR 0.93, 95% CI 0.75–1.14; respectively) and the live birth rate (OR 0.98, 95% CI 0.89–1.08; OR 0.98, 95% CI 0.86–1.12; respectively) of IVF/ICSI. Maternal alcohol consumption was negatively associated with pregnancy after IVF/ICSI treatment (OR 0.83, 95% CI 0.69–1.01). Paternal alcohol consumption was negatively associated with partner's live birth after IVF/ICSI treatment (OR 0.88, 95% CI 0.79–0.99). Compared with abstainers, the chance of achieving a pregnancy after IVF/ICSI treatment decreased by 7% for women who consumed 84 g alcohol per week (OR 0.93, 95% CI 0.90–0.98), and the chance of partners achieving a live birth decreased by 9% for men who consumed 84 g alcohol per week (OR 0.91, 95% CI 0.88–0.94). Conclusions There was no association between caffeine consumption and pregnancy or live birth rate of IVF/ICSI. Women's alcohol consumption was associated with decreased pregnancy rate after IVF/ICSI treatment when weekly consumption was greater than 84 g. Men's alcohol consumption was associated with decreased live birth rate after IVF/ICSI treatment when weekly consumption was greater than 84 g.